Illegal Logging Crimes In Forest Areascriminal Law - Muhammad Hendra; Hizra Mariani (Program Pascasarjana UIN Sumatera Utara Medan, 2020)
This study aims to determine the process of overcoming and handling carried out by the Forestry Police of the Sulawesi Regional Forestry Security and Law Enforcement Center in Handling Illegal Logging Cases. This study uses an empirical juridical research method. The research location is the Sulawesi Regional Forestry Security and Law Enforcement Center. The data sources used are primary data, namely data obtained directly from sources at the research location, secondary data is data obtained through library studies, namely reviewing literature, articles, coverage, and laws and regulations. The data collection techniques used are library research and field research that includes interviews and documentation. The data analysis technique used is quantitative. The results of this study indicate that MB is the owner of the wood as well as a suspect in illegal logging and Rasdin as the publisher of the wood document. In deciding a case, law enforcement should always carry out the mandate of the Republic of Indonesia Law No. 18 of 2013 concerning the prevention and eradication of forest destruction. In addition, law enforcement must be more consistent in this illegal logging, which aims to protect forests. from the destruction and damage to forests and the surrounding environment